Women`s construction in the Qur`an: comparative study of al-sha`rawi`s al-mar`ah fi al-Qur`an and al-aqqad`s al-mar`ah fi al-Quran - Mohammad Taufikurohman (Program Pascasarjana UIN Sunan Kalijaga, 2018)
yt 1./ws.c.1